Parturition induction in ewes by a progesterone receptor blocker, aglepristone, and subsequent neonatal survival: Preliminary results - Ozalp, R. G.; Yavuz, A.; Orman, A.; Seker, I.; Kucuksen, D. Udum; Risvanli, A.; Wehrend, A. (Elsevier Science Inc, 2017)
The clinical effects of aglepristone treatment to induce parturition in ewes and their newborns were reported. Three experimental groups were defined: group AG5 (n = 5), group AG10 (n = 5), and group CG (n = 5) in which ewes were injected twice with 5, 10 mg/kg of aglepristone, and saline solution of ewes, respectively. Different parameters associated with parturition in ewes and their newborns were investigated. Serum progesterone, oxytocin, and free and conjugated total estrogens were measured after treatments until parturition. No statistical difference was found from first aglepristone administration to onset of lambing between AG5 and AG10 (23.90 +/- 6.20, 40.00 +/- 6.71 hours). Parturition induction in two groups shortened the gestational length significantly compared with the control group (P = 0.003). Dystocia was observed in two ewes in group AG10. The placental weight showed statistically significant difference only between the AG10 and CG (P = 0.039), but no difference was observed in the placental expulsion period between the groups. Decrease in food consumption 24 to 36 hours after parturition in all ewes and skin necrosis in an ewe in group AG5 were observed. Progesterone concentration was significantly lower in AG5 than that in ewes in group AG10 and CG (P < 0.05). No difference was observed in concentrations of free total estrogens and oxytocin between groups. The body temperature of lambs was significantly different between AG10 and CG groups both right after (P = 0.011) and 12 hours after parturition (P = 0.014). The lambs in CG had the highest mean birth weight (4.29 +/- 0.28 kg), which was significantly different from the induced groups. No significant difference of blood pH and blood gases values between groups was identified both at birth and 12 hours after parturition for lambs. Significant differences could clearly be observed in total protein and blood urea nitrogen and total protein findings 12 hours after parturition (P < 0.05), whereas no difference was found in blood glucose, albumin, inorganic phosphor, triglyceride, or total cholesterol parameters. The results of this study show that the administration of aglepristone to induce parturition can precisely control lambing time without any side effects in either mothers or lambs. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Ewe; Aglepristone; Parturition induction; Lambs